PENGARUH KOMITMEN KARYAWAN DAN KOMUNIKASI TERHADAP PRESTASI KERJA KARYAWAN PADA KOPERASI CU MANDIRI UNIT DAERAH TEBING TINGGI - Ritonga, Sinar (Jurnal Manajemen dan Bisnis, 2019)
This study aims to test and analyze Employee Commitment and Communication to Employee Performance at Cooperative CU Mandiri Unit Areas Tebing Tinggi. The data was collected through interviews and questionnaires distributed to 67 employees at CU Mandiri Cooperative Unit of Tebing Tinggi District. Data analysis in this study using SPSS version 20. The technique used is the method of sampling and data testing techniques used in this study include the validity test and reliability test, the classical assumption test. Multiple linear regression analysis, and hypothesis test also conducted to test and prove hypothesis in research. From the result of partial testing (t test) shows tcount (2,240> ttable (1,669) and its significance level is 0,018 <0,05 proves that employee commitment have positive and significant effect to employee performance tcount (6,706)> ttable (1,669 ) and its significance level is 0.000 <0.05 proves that communication has a positive and significant effect on employee performance F Test shows Fcount> Ftable is 46,209> 3,14 and its significance level (0,000 <0,05) proves that employee commitment and communications have a positive and significant influence simultaneously on employee performance. From result of discussion obtained by equation of doubled linear regression is Y = 6,763 + 0,365X1 + 0,767X2 + ÎµÎ¯. Result of analysis indicate that employee commitment have positive effect to employee performance, and communication have positive effect to employee performance on CU Mandiri Cooperative Unit of Tebing Tinggi Region. Coefficient of determination equal to 0,591 mean 59,1% that variation of employee work performance can be explained by variation of employee commitment and communication equal to 59,1% rest 40,9% explained by other variable not included in this research.